Strength training for distance runners - Westcott, W. L. (1998)
On the sense, advantages, disadvantages and methods of strength training for distance runners (males and females). - Recommendation of Strength Training Programmes, - Recommendation of Strength Exercises For Runners (Nautilus machines and free weights for differtent muscle groups).